2012
DOI: 10.1007/s11746-012-2126-7
|View full text |Cite
|
Sign up to set email alerts
|

Oil, Fatty Acid Profile and Karanjin Content in Developing Pongamia pinnata (L.) Pierre Seeds

Abstract: Oil content, fatty acid composition and karanjin content were studied in developing pongamia seeds, at intervals of 3 weeks from 30 weeks after flowering up to 42 weeks. Three marked stages in seed development were observed at the early green pod stage, the middle half brown stage and the late dark brown stage. Significant variation in seed biomass, pod and seed characteristics were observed. A significant (P \ 0.01) decrease in the moisture content of the seeds was observed during seed development. The oil co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 32 publications
4
23
2
Order By: Relevance
“…The diameter of the oil bodies observed in pongamia seed was at par with the other diverse species [7]. The diameter of the oil bodies (0.3 to 1.2 lm) was correlated to the high oil content of the mature seed (36.53 %) [13]. The correlation between high oil content and small oil bodies was also reported in Brassica napus [38].…”
Section: Ultrastructure Of Developing Seedssupporting
confidence: 53%
See 3 more Smart Citations
“…The diameter of the oil bodies observed in pongamia seed was at par with the other diverse species [7]. The diameter of the oil bodies (0.3 to 1.2 lm) was correlated to the high oil content of the mature seed (36.53 %) [13]. The correlation between high oil content and small oil bodies was also reported in Brassica napus [38].…”
Section: Ultrastructure Of Developing Seedssupporting
confidence: 53%
“…The previous study on pongamia showed that pod length and breadth did not vary much however the pod thickness, seed length, breadth and thickness increased from 30 to 42 WAF. The oil content increased with seed maturity and the oleic acid content remained high at the end of pod maturity while karanjin content varied significantly across different stages of pongamia seed development [13]. Localisation of seed storage reserves in pongamia showed a marked compartmentation similar to that observed in Phaseolus vulgaris [10].…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…First, the Pongamia trees are capable of producing high yield of seeds with high contents of non-edible oil, which can be readily extracted and converted into biodiesel by transesterification (Karmee and Chadha 2005;Naik et al 2008). Second, the Pongamia seed oil possesses a high proportion of monounsaturated oleic acid and a relatively low amounts of saturated and polyunsaturated fatty acids (Bala et al 2011;Pavithra et al 2012), which may endow the biodiesel products with lower cloud and pour points. Third, being a tree legume, the Pongamia can undergo biological nitrogen fixation and thus reduce the application of nitrogen fertilizers, which may in turn mitigate the deleterious environmental impacts of greenhouse gas emissions or water pollution (Jensen et al 2012;Biswas and Gresshoff 2014;Gresshoff et al 2015).…”
Section: Introductionmentioning
confidence: 99%